Religiosity and quality of life in breast cancer patients - Aukst-Margetić, Branka (Array, 2009)
Our aim was to assess relations between the quality of life and religiosity in breast cancer patients. The participants were 115 consecutively admitted female in-patients with breast cancer in the radiotherapy unit in the course of six months. The measures used were Santa Clara Strength of Religious Faith Questionnaire (SCSORF), World Health Organisation Well-Being Index Five (WHO-WBI 5) and International Breast Cancer Study Group Quality of Life (IBCSG-QL) Questionnaire. The participants responded on three statements relating to religious coping with cancer. Moderate religiosity was associated with perception of worse physical health. The statement "the illness decreased my faith" was associated with worse quality of life (QOL) domains: less well-being, more pain, poor physical health, more effort to cope, worse fatigue and less general satisfaction. The statement "the faith helps me in illness" was associated with higher social support.